Integration of Customer Segmentation and Marketing Mix to Enhance Product Quality Superiority in Competitive Markets - Gunawan Wibisono; Sri Handoko (Universitas Sains dan Teknologi Komputer, 2026)
Increasing market competition requires firms to continuously develop superior product quality by aligning marketing strategies with diverse customer preferences in order to sustain competitive advantage. This study aims to empirically examine how the integration of customer segmentation and marketing mix strategies influences product quality superiority in competitive markets. The methodology used is quantitative and explanatory in nature with the help of structural equation modeling (SEM) with survey results obtained from 342 consumers in the manufacturing and modern retail industries. The findings indicate that customer segmentation is an important variable in the formation of the marketing mix and that both variables are positively contributing to the achievement of product quality superiority. The research contributes to the marketing discipline by proposing an integrated quantitative model that is used to explain the formation of sustainable product quality superiority with managerial implications for businesses that aim to enhance their competitive advantage with the help of marketing strategies.